Evolutionary approach to the educational content structure design automation problem solution - Belomoytsev D.E. (Научно-технический вестник Брянского государственного университета)
The educational courses effective formation problem at remote form of education is designated. Approach to educational elective courses content formation is considered. The evolutionary technique of drawing up courses is offered. Features of educational content multidimensional representation are given. The way of automation of design of individual programs of training is presented.